Modern trends in the health care system of Russia: drop or rise - Yuliya Zh. Sadykova (Статистика и экономика)
In the period of the existence of post-soviet Russia, the health care system has remained and remains one of the most important and, at the same time, the problem element of it. We have to admit that not always medical services, offered by our state, are positive, if we consider them, for example, through the concept of “quality”. Undoubtedly, this is determined by the existing medical structure, starting with the number of different hospital establishments and ending with the degree of qualification and competence of medical specialists.Thus, the purpose of this article is a comprehensive analysis of the healthcare system that was established in the Russian Federation in 1990–2015, the object of the study is the entire Russian health care system, and the subject is specific statistical data on the hospital beds and hospitals in Russia.Problems of health development, as well as various methodological issues of statistical research, including the accounting of hospital facilities, hospital beds, doctors in the context of specialties, morbidity are considered in the works of both domestic and foreign scientists (V.Medic, M. Tokmachev, G. Ulumbekova, S. Banin, McKee Martin and others).The main directions of development of the national medicine for the specified period of time, its characteristic features and problems of concern that cause dysfunction in the work of the health care protection mechanism for the citizens were identified in the context of the dynamics in such statistical indexes as the total number of hospital and outpatient clinics, hospital beds in them, the number of doctors and the state of morbidity of the population, published by the Federal State Statistics Service.As a research task, attempts were made to assess the impact of changes in these indexes on the state of Russian health care over the period as a whole. Moreover, the work revealed the main content concepts on this topic, explained the nominal structure of the existing nomenclature, provided methodological explanations for the specifics of the changes that were taking place, and indicated the measure of the implementation of the state program “Health Development”. The tools for the study were tables and graphs of visualizing informative data, as well as various formulas that form the basis of health statistics, and analytical methods for studying the processes occurring in a given medium. Based on the results of the study, a number of specific patterns between the phenomena and indexes were identified, as well as a description of the current trends in the sphere of the Russian medicine in the context of the bed capacity for individual medical specializations, the number of hospitals and medical practitioners.